The seven crystal balls - Hergé, 1907-1983 (Hergé, 1907-1983. Aventures de Tintin., 2014)
Tintin, Snowy, and Captain Haddock become involved when a mysterious illness strikes the members of an archaeological expedition who have just returned from Peru and Bolivia.